2007
DOI: 10.1016/j.ultsonch.2006.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hydrodistillation and ultrasonic solvent extraction for the isolation of volatile compounds from two unifloral honeys of Robinia pseudoacacia L. and Castanea sativa L.

Abstract: A comparative study of ultrasound-assisted extraction (USE) with the mixture pentane:ether (1:2) and hydrodistillation (HD) with the same trapping mixture is presented for the isolation of volatile compounds from two unifloral honeys of Robinia pseudoacacia L. and Castanea sativa L. All HD isolates contained many thermally derived artefacts (especially phenylacetaldehyde with lower percentages of furfural, cis- and trans-linalool oxides and others). USE method gave the most representative profile of all honey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
1
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 18 publications
1
42
1
4
Order By: Relevance
“…Of the organic acids identified, hexadecanoic acid was present in apple honey (M. domestica) (0.0162 µg/g) and in cherry honey (P. avium) (0.0762 µg/g), acetic acid (0.0519 µg/g) and stearic acid (0.0011 µg/g) only in cherry honey and apple honey, respectively, while there was no organic acid found in saffron honey (C. sativus). These results were in agreement with the studies conducted by Jerkovic et al [11] and Lusic et al [34] which found hexadecanoic acid in the unifloral honeys of black locust (Robinia pseudoacacia L.), chestnut (C. sativa L.) and fir honeydew honey (Abies alba), respectively. Hexadecanoic acid has been reported in apple blossom (M. domestica) as well as in Mahaleb cherry (Prunus mahaleb), thus revealing similarity of both volatile profiles [23,40].…”
Section: Honey Markers For the Characterization Of Different Uniflorasupporting
confidence: 93%
“…Of the organic acids identified, hexadecanoic acid was present in apple honey (M. domestica) (0.0162 µg/g) and in cherry honey (P. avium) (0.0762 µg/g), acetic acid (0.0519 µg/g) and stearic acid (0.0011 µg/g) only in cherry honey and apple honey, respectively, while there was no organic acid found in saffron honey (C. sativus). These results were in agreement with the studies conducted by Jerkovic et al [11] and Lusic et al [34] which found hexadecanoic acid in the unifloral honeys of black locust (Robinia pseudoacacia L.), chestnut (C. sativa L.) and fir honeydew honey (Abies alba), respectively. Hexadecanoic acid has been reported in apple blossom (M. domestica) as well as in Mahaleb cherry (Prunus mahaleb), thus revealing similarity of both volatile profiles [23,40].…”
Section: Honey Markers For the Characterization Of Different Uniflorasupporting
confidence: 93%
“…H 2 O in a 100-ml flask. MgSO 4 (1.5 g) was added, and each sample was extensively vortexed [10] [28]. Different extraction solvents were separately used for USE: 1) a mixture of pentane/Et 2 O 1 :2 (v/v), 2) pentane, and 3) Et 2 O (applied to the samples after sonication with pentane and after removing the pentane extract).…”
Section: Experimental Partmentioning
confidence: 99%
“…Only a few compounds seem to be really specific, and many of them can be found in variable concentrations in various honey types. Ultrasonic solvent extraction (USE) is a suitable method to obtain reliable honey fingerprint of more and less volatile (low-and high-molecular) compounds in comparison with other methods such as hydrodistillation or simultaneous distillation -extraction [9] [10].…”
mentioning
confidence: 99%
“…H 2 O in a 100-ml flask. MgSO 4 (1.5 g) was added, and each sample was extensively vortexed [19] [20]. Different extraction solvents were separately used: a mixture pentane/Et 2 O 1:2 (v/v), pentane, and Et 2 O (applied on the samples after sonication with pentane and after removing the pentane layer).…”
Section: Experimental Partmentioning
confidence: 99%